161k views
17 votes
-x/11 - 13 = -1

---
what does "x" equal

2 Answers

13 votes
-132 i think is the correct answer
User RickHigh
by
5.6k points
11 votes

Answer:


x = -132

Explanation:

Step 1: Add 13 to both sides


-(x)/(11) + (-13 + 13) = (-1 + 13)


-(x)/(11) = 12

Step 2: Multiply both sides by -11


-(x)/(11) * (-11) = 12* (-11)


x = -132

Answer:
x = -132

User Alexander Sysuiev
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.